INOVASI PENDIDIKAN INKLUSIF: ANALISIS KEBUTUHAN MEDIA PEMBELAJARAN INTERAKTIF BERBASIS TEKNOLOGI UNTUK SISWA TUNARUNGU - Annisa Azzahra; Venissa Dian Mawarsari; Iswahyudi Joko Suprayitno (Jurnal Genta Mulia, 2025)
This study aims to evaluate the need for interactive learning media in learning mathematics for deaf students. This research uses descriptive qualitative method with data collection techniques through observation, interviews with math teachers, and questionnaires regarding the needs of deaf students. The subjects of this study were deaf students and Phase E math teachers in one of the special schools in Semarang City. The results showed that technology-based learning media has been used in several subjects, but it is not interactive and has never been used in learning mathematics. Whereas deaf students prefer and are interested in interactive and technology-based learning media. The interview results stated that teachers are interested in using technology-based interactive learning media in math learning to help students understand the concept of flat area material. In line with this, the results of the needs questionnaire, deaf students are 100% interested and agree with the development of technology-based interactive learning media that can maximize their visual and motor intelligence so that it can help in their learning process on flat area material.